Coded Territories: Tracing Indigenous Pathways in New Media Art - Loft, Steve; Swanson, Kerry (University of Calgary Press, 2014)
This collection of essays provides a historical and contemporary context for Indigenous new media arts practice in Canada. The writers are established artists, scholars, and curators who cover thematic concepts and underlying approaches to new media from a distinctly Indigenous perspective. Through discourse and narrative analysis, the writers discuss a number of topics ranging from how Indigenous worldviews inform unique approaches to new media arts practice to their own work and specific contemporary works. Contributors include: Archer Pechawis, Jackson 2Bears, Jason Edward Lewis, Steven Foster, Candice Hopkins, and Cheryl L'Hirondelle.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Shapeshifters, Time Travellers and Storytellers - Hopkins, Candice; Swanson, Kerry (Royal Ontario Museum, 2008)
"Incorporating evocative objects from the Museum's collections, this thought-provoking exhibition presents eight contemporary Aboriginal artists whose works explore the ways in which past and present continue to merge and shape one another. This exhibition features eight striking installations, including more than 25 individual artworks by internationally renowned artists Suvinai Ahsoona, Faye HeavyShield, Cheryl L’Hirondelle, Isuma Productions (Zacharias Kunuk and Norman Cohn), Brian Jungen, Alan Michelson, Nadia Myre and Kent Monkman. Five of the eight works, which include video, sound, sculpture, drawings, painting and performance art, were created specifically for this exhibition. Co-organized by the Royal Ontario Museum’s Institute for Contemporary Culture and the imagineNATIVE Film + Media Arts Festival. Co-curated by Kerry Swanson and Candice Hopkins.
Keywords: _Nettoyé

Indigenous Feature Film Production in Canada: A National and International Perspective - Goulet, Danis; Swanson, Kerry (ImagineNATIVE Film + Media Arts Festival, 2014)
The goal of this research is to examine Aboriginal feature film production in Canada, specifically within the genre of drama. This report documents the rise of Indigenous cinema worldwide and examines Canada's public funding landscape including funding allocations to Aboriginal feature film production from Canada's public funders of film over a five-year period from 2007 to 2012. This report also examines the barriers to feature film production for Aboriginal content creators in Canada, and suggests areas of opportunity that can be targeted in order to boost production in this sector. Aboriginal film production is a relatively young sector, with scarce research existing on the industry. To address this gap in the available information on the sector, the researchers expanded the scope of the study beyond public funding agencies in Canada to include data from public funding agencies in Australia and New Zealand. Aboriginal feature film production in Canada is situated within a global Indigenous cinema context. Australia and New Zealand, in particular, are two pillars of global Indigenous film that offer a realistic point from which to compare Canada's progress. As a result, data from Australia and New Zealand are included in the study, as well as one model in the United States.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé